Killer floods [videorecording (DVD)] - Kew, Elliot, 1969-; Sechler, Craig (PBS Distribution, 2018)
Scientists investigate floods occurring in the remote past that evidence shows to have been of a magnitude far greater than even the more extreme floods of today. The possibility of such floods recurring and the connection between cataclysmic floods and climate change are discussed.